2021
DOI: 10.1097/cd9.0000000000000038
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19, the Pandemic of the Century and Its Impact on Cardiovascular Diseases

Abstract: COVID-19 caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection likely ranks among the deadliest diseases in human history. As with other coronaviruses, SARS-CoV-2 infection damages not only the lungs but also the heart and many other organs that express angiotensin-converting enzyme 2 (ACE2), a receptor for SARS-CoV-2. COVID-19 has upended lives worldwide. Dietary behaviors have been altered such that they favor metabolic and cardiovascular complications, while patients have avoided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 335 publications
(868 reference statements)
1
8
1
Order By: Relevance
“…p t e d f o r P u b l i c a t i o n who survived COVID-19 and those died because of COVID-19. A statistically significant association between age and COVID-19 positivity was observed in females, but not in the male gender.Clinical observations indicated that advanced age and male gender increased the risk of COVID-19 4,14. Different from these observations, most patients in the current study were females, and, similar to these observations, COVID-19-positive females were older.…”
supporting
confidence: 66%
“…p t e d f o r P u b l i c a t i o n who survived COVID-19 and those died because of COVID-19. A statistically significant association between age and COVID-19 positivity was observed in females, but not in the male gender.Clinical observations indicated that advanced age and male gender increased the risk of COVID-19 4,14. Different from these observations, most patients in the current study were females, and, similar to these observations, COVID-19-positive females were older.…”
supporting
confidence: 66%
“…Among these possibilities, the latter seems adequate to explain at least partially the gender-related observations. Furthermore, since the hormone steroid, testosterone (TEST) plasmatic concentrations decrease with aging and the presence of comorbidities (obesity, diabetes mellitus, and cardiovascular diseases) increases during the same period, both circumstances might worsen SARS-CoV-2 patients' prognosis (Figure 1) [9][10][11][12]. Understandably, multiple studies have been carried out trying to predict the outcome of the disease in patients.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, in our study, on the multivariable analysis emerged that high peak troponin was significantly correlated with in hospital mortality and other outcomes, indicating that CAC does not completely identify patients at risk of cardiovascular events because probably it does not reveal soft, unstable plaques that are more sensitive to external stresses. 30 …”
Section: Discussionmentioning
confidence: 99%